Proses Islamisasi Melalui Jalur Perniagaan di Lombok: Sebuah Analisis Historis - Ahsanul Rijal (Kalijaga Journal of Communication, 2019)
In the process of Islamizing the people of Lombok. There are many theories about the entry of Islam in Lombok through commercial channels. As one of the nations with marine wealth, before Islam entered the nation, Indonesia was known as sailors. So, in the process of entering Islam, of course it cannot be separated from marine activities and commerce. This article focuses on commercial activities as the beginning of the entry of Islam in Lombok. By using critical historical and phenomenological approaches from various historical literatures. Based on commerce in observing the process of Islamization and showing the argument that the da’wah process was preceded by economic struggle. This article strengthens the general theory that Islam was brought in by Muslim traders. Also, this article shows that Islam entered by seizing the economic base of the Indonesian people, namely agricultural and maritime commodities. This means that the beginning of Islam did not directly preach religion, but was involved in the economic activities of the people of the archipelago, then Islam was preached. This article is qualitative-descriptive, with local historical databases such as Babad Lombok and Negarakartagama.Dalam proses Islamisasi masyarakat Lombok, banyak teori mengenai masuknya Islam di Lombok melalui jalur perniagaan. Sebagai salah satu bangsa dengan kekayaan laut, sebelum Islam masuk bangsa Indonesia sudah dikenal sebagai pelaut. Maka, dalam proses masuknya Islam tentu tidak bisa lepas dari aktivitas laut dan perniagaan. Artikel ini berfokus pada aktivitas perniagaan sebagai awal masuknya Islam di Lombok. Dengan menggunakan pendekatan historis dan fenomenologis kritis dari berbagai literatur sejarah. Berbasis pada perniagaan dalam melihat proses Islamisasi serta menunjukkan argumentasi bahwa proses dakwah didahului dengan perebutan ekonomi. Artikel ini memperkuat umumnya teori, Islam masuk dibawa oleh para pedagang muslim.  Juga, dalam artikel ini menunjukkan bahwa Islam masuk dengan merebut basis ekonomi masyarakat nusantara yaitu komoditas pertanian dan maritim. Artinya, awal Islam masuk tidak langsung mendakwahkan agama, melainkan ikut terlibat dalam aktivitas ekonomi masyarakat nusantara, kemudian barulah Islam didakwahkan. Artikel ini menggunakan kualititaf-deskriptif, dengan basis data sejarah lokal seperti Babad Lombok dan Negarakartagama.